An Experimental and Theoretical Investigation of 1-Butanol Pyrolysis - Rosi, Marzio; Skouteris, Dimitris; Balucani, Nadia; Nappi, Caterina; Faginas Lago, Noelia; Pacifici, Leonardo; Falcinelli, Stefano; Stranges, Domenico (Frontiers in Chemistry, 2019)
Bioalcohols are a promising family of biofuels. Among them, 1-butanol has a strong potential as a substitute for petrol. In this manuscript, we report on a theoretical and experimental characterization of 1-butanol thermal decomposition, a very important process in the 1-butanol combustion at high temperatures. Advantage has been taken of a flash pyrolysis experimental set-up with mass spectrometric detection, in which the brief residence time of the pyrolyzing mixture inside a short, resistively heated SiC tube allows the identification of the primary products of the decomposing species, limiting secondary processes. Dedicated electronic structure calculations of the relevant potential energy surface have also been performed and RRKM estimates of the rate coefficients and product branching ratios up to 2000 K are provided. Both electronic structure and RRKM calculations are in line with previous determinations. According to the present study, the H2O elimination channel leading to 1-butene is more important than previously believed. In addition to that, we provide experimental evidence that butanal formation by H2 elimination is not a primary decomposition route. Finally, we have experimental evidence of a small yield of the CH3 elimination channel.